Data sharing and data standards for metabolomics: where are we now? - Salek, Reza (Henry Stewart Talks, 2018)
Current state of data sharing and exchange standards, Making efficient use of data for metabolomics, Metabolomics standard initiative, Data sharing repositories, Metabolite annotation/identification, Capturing metadata, Metabolomics identification, Quality control in metabolomics, Journals for metabolomics data-sharing and reuse